Nurturing high-performance sport coaches` learning and development using a narrative-collaborative coaching approach - Milistetd, M.; Peniza, L.; Trudel, P.; Paquette, K. (LASE Journal of Sport Science, 2018)
For several years, sport coach education has meant the development of specific training programs and subsequent certifications. Given the phenomena of globalization and advances in technology, it is now easy to gain access to a vast amount of information that is constantly being updated. This has a significant impact on education in general, including the sporting world. In this article, we present, using the literature, coach education and development as a lifelong learning journey, and we highlight who are the key people to help/support coaches in their learning journey. Then we focus on a new actor; a coach of coaches we call the `Personal Learning Coach`. By using a narrative coaching approach, we argue that personal learning coaches can offer the sport coaches a safe and demanding environment for a co-creation of knowledge. We conclude the article by presenting a case study in which we describe the coaching conversations between a high-performance tennis coach and his personal learning coach over a period of six months.